Psychological Problem Of The Main Character In Shutter Island Movie: Psychoanalysis Approach - Nur, Luthfiah (CV. Kalimasada Group Profesional, 2023)
This study aims to analyze and identify the psychological aspects of Sigmund Freud's psychoanalysis of the main character in the film Shutter Island, starring Leonardo DiCaprio as Edward ‘Teddy’ Daniels, who suffers from delusional disorders due to past conflicts. Teddy’s internal conflict causes him to experience delusions that lead to subconscious conflicts that trigger inappropriate and irrational beliefs that make it difficult for him to accept reality and control his id, ego and superego. Qualitative methods are used in this research because this research does not refer to numbers and statistical calculations. The writer analyzes the main characters in the film in depth based on dialogue scripts and storylines. Based on the research results, psychoanalytic data was found on the main character with 5 id data, 3 ego data, 6 superego data, with Id as part of psychoanalysis which dominates the main character’s personality caused by unresolved subconscious conflicts by always trying to ignore and reject reality by fulfilling the will of the id which is contrary to the state of reality. Keywords: Psychoanalysis; Sigmund Freud; Movie